An Assessment of Factors Leading to Motivation and Stress among Employees in Private Banks - Dr. Sushant Waghmare, Mr. Sushrut Rahul (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Private banks play a vital role in the economy. They are highly competitive organizations requiring great levels of performance from their employees. In order to keep employees motivated, they must be satisfied and happy at the workplace. The study delves into the various factors that motivate and de-motivate the employees. It also focuses upon the expectations that the employees have from their organization and possible areas wherein improvements can be made. The research was carried out using a self-administered questionnaire and secondary sources of data were used for literature review. It is observed from the analysis that more or less the employees are satisfied at the workplace however, face issues with the relentless hours of work and this in turn, affects their work-life balance. It is also concluded that the challenging work is the primary motivator and lack of monetary compensation is the primary de-motivator. It is also inferred from the data that, incentives and open recognition are the key expectations that employees have from their organization.